Synergy assessment in hybrid Ultra-High Performance Fiber-Reinforced Concrete (UHP-FRC). (February 2018) - Fantilli, Alessandro P.; Kwon, Sukmin; Mihashi, Hirozo; Nishiwaki, Tomoya
Abstract: Ultra-High Performance Fiber-Reinforced Concretes (UHP-FRC) subjected to uniaxial tensile loads are investigated in the present paper. The study comprises a new procedure to assess the effectiveness of the hybridization, herein obtained by reinforcing UHP-FRC with micro and macro steel fibers. A comprehensive experimental campaign is also performed on monofiber and hybrid UHP-FRC. In all the concretes, the distance between the cracks and the minimum fiber volume fraction, which produces strain hardening response and multiple cracking, are theoretically and experimentally evaluated. If the bond parameter of the macro-fibers is properly calculated, the results of the analytical model, in terms of crack-spacing vs. fiber volume fraction, are in good agreement with the test data. Moreover, to increase the number of the cracks, and to reduce crack spacing, the hybridization is suitable only when the amount of macro-fibers is within a well-defined range.